2018
DOI: 10.1080/20002297.2018.1442089
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide GH12 suppresses cariogenic virulence factors of Streptococcus mutans

Abstract: Cariogenic virulence factors of Streptococcus mutans include acidogenicity, aciduricity, and extracellular polysaccharides (EPS) synthesis. The de novo designed antimicrobial peptide GH12 has shown bactericidal effects on S. mutans, but its interaction with virulence and regulatory systems of S. mutans remains to be elucidated. The objectives were to investigate the effects of GH12 on virulence factors of S. mutans, and further explore the function mechanisms at enzymatic and transcriptional levels. To avoid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 59 publications
1
81
0
Order By: Relevance
“…In our previous studies, the antimicrobial peptide GH12 showed rapidly acting antibacterial efficacy against S. mutans by inducing lysis and pore formation in the cytomembrane [20]. In addition, the virulence factors of this principle caries pathogen were also suppressed [21]. In the current article, aimed at promoting the clinical effect of GH12, its anticaries efficacy was assessed in a well-established rat model, and the observed effect was further supported through in vitro S. mutans biofilm assays.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In our previous studies, the antimicrobial peptide GH12 showed rapidly acting antibacterial efficacy against S. mutans by inducing lysis and pore formation in the cytomembrane [20]. In addition, the virulence factors of this principle caries pathogen were also suppressed [21]. In the current article, aimed at promoting the clinical effect of GH12, its anticaries efficacy was assessed in a well-established rat model, and the observed effect was further supported through in vitro S. mutans biofilm assays.…”
Section: Discussionmentioning
confidence: 78%
“…The quantitative real-time PCR was performed using a CFX96 Real-Time System (C1000™ Thermal Cycler; Bio-Rad, Hercules, CA). In brief, 25 µL of the mixture containing 12.5 µL of SYBR® Premix Ex Taq ™ II (RR820A; Takara Bio, Shiga, Japan), 1 µL of specific forward primer (10 µM), 1 µL of specific reverse primer (10 µM), 1 µL of the template, and 9.5 µL of double distilled water were placed in each well with the same cycle conditions as used in a previous study [21]. The bacterial counts were determined from standard curves and the results were displayed as lg (cells/mL).…”
Section: Dna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Forward primer Reverse primer 16S rRNA [28] AGCGTTGTCCGGATTTATTG CTACGCATTTCACCGCTACA Ldh [28] AAAAACCAGGCGAAACTCGC CTGAACGCGCATCAACATCA atpD [28] TGTTGATGGTCTGGGTGAAA TTTGACGGTCTCCGATAACC gtfB [29] TACACTTTCGGGTGGCTTGG AGAAGCTGTTTCCCCAACAGT gtfC [29] AGCAGATTCAACTGACGACCG TCAGTAACAGTGGCGGTTGG gtfD [29] TGCAAGCGACGGAAAACAAG GCCTGTCAGAGCTTCACCAT vicR [28] CGTGTAAAAGCGCATCTTCG AATGTTCACGCGTCATCACC liaR [28] CATGAAGATTTAACAGCGCG CGTCCTGTGGCACTAAATGA comD [28] TTCCTGCAAACTCGATCATATAGG TGCCAGTTCTGACTTGTTTAGGC comE [28] TTCCTCTGATTGACCATTCTTCTG GAGTTTATGCCCCTCACTTTTCAG expression (which was variable), as the concentration of oxyresveratrol also increased. In brief, the expression of glucosyltransferase S (gtfD) and lactate dehydrogenase (ldh) increased at lower concentrations of oxyresveratrol (62.5 and 125 lg ml À1 ) and then showed a slight decrease at the high concentration of oxyresveratrol (250 lg ml À1 ), which was still higher than the control.…”
Section: Genementioning
confidence: 99%